Contribution of fine needle aspiration cytology to diagnosis and management of thyroid disease. Issue 5 (May 1992) - Godinho-Matos, L; Kocjan, G; Kurtz, A
Abstract : AIMS: To determine the role of fine needle aspiration cytology (FNAC) in the diagnosis and management of thyroid disease. METHODS: Clinical histories of 144 patients who had undergone FNAC of the thyroid were analysed. Clinical presentation, non-invasive investigations including hormone assays, ultrasound, and isotope scan procedures were compared with FNAC diagnoses in all cases and with histological diagnosis in the 28 cases (19%) that had undergone surgery. Clinical management was decided upon combining all of the above investigations. The relative contribution of the FNAC was divided into: essential, additional and non-contributory, misleading. RESULTS: FNAC diagnoses included: 29 (16%) benign colloid goitre, 56 (39%) benign cystic goitre, 24 (17%) thyroiditis, and 22 (15%) neoplasms. Nineteen (13%) of the specimens were unsatisfactory. When compared with clinical diagnoses based on non-invasive diagnostic investigations FNAC represented no improvement on the diagnosis of benign colloid/cystic goitre (55% v 54% respectively). It represented an improvement on the diagnosis of thyroiditis (9% v 17% respectively). FNAC decreased clinically suspicious lesions in which 22 neoplasms were diagnosed from 37% to 15%. Eleven patients with neoplasms underwent surgery and neoplasms were confirmed histologically. Others including lymphoma, metastatic carcinoma, and analplastic carcinoma were managed conservatively. There were four false negative FNAC diagnoses (3%) in clinically suspicious lesions, found on histology to be benign follicular adenomas. CONCLUSIONS: FNAC had an essential role in the diagnosis and management of 23% of our patients, a confirmatory role in 61% of patients, a non-contributory role in 13% when specimens were inadequate, and was misleading in 3% where results were false negative. The positive identification of thyroiditis and neoplasia stands on its own as a justification for FNAC.